2012
DOI: 10.1007/s10237-012-0438-z
|View full text |Cite
|
Sign up to set email alerts
|

Multiaxial mechanical behavior of human fetal membranes and its relationship to microstructure

Abstract: This study was directed to the measurement of the mechanical response of fetal membranes to physiologically relevant loading conditions. Characteristic mechanical parameters were determined and their relation to the microstructural constituents collagen and elastin as well as to the pyridinium cross-link concentrations analyzed. 51 samples from twelve fetal membranes were tested on a custom-built inflation device, which allows mechanical characterization within a multiaxial state of stress. Methods of nonlinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…The work by Arikat et al [8] provided evidence of the rupture sequence of FM by video docu mentation of puncture tests, showing that chorion ruptures first. This is in contrast to observations from recent inflation and uniaxial tension experiments on intact FM as well as on separate amnion and chorion layers [16][17][18],…”
Section: Introductioncontrasting
confidence: 85%
“…The work by Arikat et al [8] provided evidence of the rupture sequence of FM by video docu mentation of puncture tests, showing that chorion ruptures first. This is in contrast to observations from recent inflation and uniaxial tension experiments on intact FM as well as on separate amnion and chorion layers [16][17][18],…”
Section: Introductioncontrasting
confidence: 85%
“…Finally, λ was calculated as current divided by initial width. For inflation experiments, membrane tension was evaluated as described in [31] from pressure values and current curvature of the specimen. The apex displacement d was quantified with a custom-made algorithm in Matlab (The MathWorks Inc., Massachusetts, USA).…”
Section: Discussionmentioning
confidence: 99%
“…A posteriori analysis showed that by this means a nominal strain rate of approximately 0.04 s -1 was achieved over the major part of the loading phase. Additionally, creep inflation tests (I) were performed with our custom-built inflation device [31] modified in order to perform creep experiments with a fast initial loading: a large reservoir filled with physiological saline solution and placed on a platform with an adjustable vertical position, was connected to the inflation chamber through a tube equipped with a valve. The reservoir was placed at a specific height to generate a target pressure in the chamber within a very short time of the opening of the valve.…”
Section: Creep Experimentsmentioning
confidence: 99%
See 2 more Smart Citations